NILAI FILOSOFIS DAN TATA CARA PEMBANGUNAN "PELINGGIH GEDONG SAREN" - I Nyoman Gde Suardana; I Wayan Aryawan; Desak Made Sukma Widiyani (Jurnal Anala, 2018)
The concept of Bali Building is still a tourist attraction not only for tourists but also various researchers who want to explore the meaning and function of the building. It can not be denied that the beauty of Balinese buildings is one of the factors that make up the natural beauty of Bali including the religious atmosphere in it. The house as the most dominant building in a residential area, also has its own characteristics in Bali. Rumah Bali can certainly have a place / means of worship commonly called Sanggah / Merajan. Even according to the Hindu concept, Sanggah / Merajan is the most important building in a house / residence. Pelinggih Gedong Saren is one part of Sanggah / Merajan. This building is an ancestral heritage that needs to be developed and preserved. Until now, the manuscripts that talk about Pelinggih Gedong Saren in particular are quite rare. So it is very necessary to conduct a special study on Pelinggih Gedong Saren so that later can be used as a consideration in the planning or making Pelinggih Gedong Saren in a Merajan or Sanggah. There are still many secrets and uniqueness in Pelinggih Gedong Saren, which notabena is an important building in the holy place of Hindu family. This research is a descriptive reasearch, which is intended for exploration and clarification of a phenomenon or social reality, by describing a number of variables concerning the problem and the unit under investigation. This type of research is not intended to attract a generation that causes a symptom or a social reality. Therefore, this study does not use and do not perform hypothesis testing because it is not intended to build and develop theory treasury. This study uses two types of data, namely primary and secondary. Primary data obtained from the results of research into the object (field) obtained directly through interview / interview and also observation. While the secondary data obtained from the study of literature, literature and lontar associated with this research. Furthermore, the analysis is done by descriptive analysis method that is a technique that try to describe and describe a problem (research variable) to be an analysis that able to explain each problem (research variable) is clear. In the future, the development of tourism will depend on the Spirit of Tourism itself. For Bali, known as the world's best destination, culture, customs, as well as the uniqueness of Bali that breathes Hinduism is the spirit of tourism itself. Understanding the meaning of each building that is a supporter of beauty and has an important function in the religious life of society is the long-term goal of this research. Keywords: philosophical values, development, gedong saren.